Book Review of Mary Kellogg Rice's Useful Work for Unskilled Women: A Unique Milwaukee WPA Project - (:unkn) unknown (My University, 2003)
A book review of the manuscript by Mary Kellogg Rice on “Useful Work for Unskilled Women: A Unique Milwaukee WPA Project.” Rice was a senior at Milwaukee State Teachers College during the Great Depression when her teacher asked her to help develop a Works Progress Administration project for women lacking skills for the other WPA projects operating in Milwaukee County. Within a few weeks Rice and her team of young art education graduates were training over 900 women to make useful products for the county orphanage, county hospital, local schools, and the WPA nursery schools.
Keywords: WPA; Great Depression; women's history; 1930s